Dosis de fertilizante foliar, en el rendimiento de Lactuca sativa L. lechuga, Loreto, Perú.2023 - Niño Guzman, Jorge (2023)
The research was conducted at the Faculty of Agronomy over a period of 35 days, using lettuce plants of the Grand Rapid variety. The plants were divided into four groups with four replicates, and each group received one of the following doses of foliar fertilizer: 0 ml/lt of water (T1, control), 2 ml/lt of water (T2), 4 ml/lt of water (T3), and 6 ml/lt of water (T4). A Completely Randomized Block Design (CRBD) was used, and the results demonstrated significantly that treatment T4, consisting of 6 ml of foliar fertilizer per liter of water, had a positive effect on the agronomic characteristics and yield of lettuce crops. Plants treated with this dose showed more robust growth, higher-quality foliage, and a greater lettuce production compared to the other treatments. In particular, treatment T4 exhibited a leaf weight per plant of 174 g and a plant weight of 270 g, significantly surpassing the other treatments in terms of yield. This indicates that the use of foliar fertilizer at a dose of 6 ml per liter of water significantly improved lettuce yield, promoting greater growth and biomass production. Additionally, an economic benefit of S/.38,243.00 was achieved.